2006
DOI: 10.1007/s00251-006-0139-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the catfish IGH locus: analysis of the region including the single functional IGHM gene

Abstract: The catfish IGH locus is large ( approximately 1 Mb) and complex, having undergone multiple internal duplications and transpositions. To define the structure of the locus that contains the single expressed IGHM gene, two overlapping bacterial-artificial-chromosome (BAC) clones spanning the most 3' end of the channel catfish immunoglobulin heavy (IGH) chain locus have been completely sequenced. The analyses created a contig of 257,153 bp containing 55 VH, 6 D, 12 JH genes and the IGH constant region genes encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 54 publications
4
60
1
Order By: Relevance
“…However, the complete composition of V H genes in the IgH loci has been reported only in zebrafish, three-spined stickleback and channel catfish, with 47, 49 and 55 V H genes identified, respectively [22,24,29]. It seems possible that the number of V H genes may vary in different species of teleost fish.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the complete composition of V H genes in the IgH loci has been reported only in zebrafish, three-spined stickleback and channel catfish, with 47, 49 and 55 V H genes identified, respectively [22,24,29]. It seems possible that the number of V H genes may vary in different species of teleost fish.…”
Section: Discussionmentioning
confidence: 99%
“…The catfish IgH locus is a translocon-type with three d genes linked to a m gene or pseudogene [28,29], being thus different from that in zebrafish, rainbow trout, fugu and grass carp. It is suggested that the organization of the IgH locus in different species of teleost fish may vary at least to some extent, as illustrated for the above five species of teleost fish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Point mutations similar to those at V H WRCH sequences have also been found at the WRCH within switch regions in mice, suggesting a common AID targeting method for both SHM and CSR. 41,42 Given that SHM has been found in all vertebrates including fish, whereas CSR appears limited to amphibians, birds and mammals [43][44][45][46][47] , it appears that SHM evolved earlier than CSR. In mammals, immunoglobulin switch regions appear to have further diverged to incorporate additional features, such as R-loop forming ability and cis-acting regulatory regions, which may serve to increase the overall efficiency of CSR.…”
Section: Discussionmentioning
confidence: 99%